The rhizosphere microbiome of common bean (Phaseolus vulgaris L.) and the effects on phosphorus uptake - Chiaramonte, Josiane Barros (2018)
The current population growth will demand a higher productive agriculture to full the food requirement. To supply this need and preserve the environment, many resources are applied to promote sustainable agriculture. Phosphorus depletion is the main factor that limits crops yields in tropical soils, where the pH and clay content rapid fixate this nutrient. Plant breeders aim to solve this issue by changing the plant requirements for phosphorus and adapting them to low P availability. However, with these approaches the demand for phosphorus fertilizers will continue and so the depletion of the natural deposits. In this study is proposed that plants with contrasting phosphorus uptake efficiency, i.e. P-efficient and P-inefficient, recruits distinct rhizosphere microbiome specialized in phosphorus mobilization. This hypothesis was tested growing plants in a gradient of two sources of P, triple superphosphate or rock phosphate Bayovar. Thebean rhizosphere microbiome was assessed with culture dependent and independent approaches, enzymatic assays, predictive metagenomics and networks analysis. A differential enrichment of several OTUs in the rhizosphere of the P-inefficient common bean genotype, and the enrichment of bacterial chemotaxis functions and functions involved in phosphorus mobilization suggest that this genotype has superior communication with the rhizosphere microbiome and is highly dependent on it for phosphorus mobilization. As a proof of concept, the P-efficientefficient genotype was sown in soil previously cultivated with P-inefficientinefficient genotype. The results showed that P-efficientefficient genotype positively responded to the modified rhizosphere in early stages, that is, the microbiome selected and enriched by the P-inefficient genotype improved the P uptake in the genotype cultivated afterwards in the same soil. Taken collectively, these results suggest that plants partly rely on the rhizosphere microbiome for P uptake and that the exploration of these interactions during plant breeding would allow the selection of even more efficient genotypes, leading to a sustainable agriculture by exploring soil residual P.